Zoning Policy in Promoting Educational Equality: Analytical Review in the Context of Policy Innovation (Agile Governance and Innovation Measurement Journal, 2024)
Policy formulation is the essential stage in the policy-making process. The reason for this is that policy formation is the primary phase that will impact the success of subsequent stages. Policy development enables the government to systematically evaluate and identify societal issues. Policy formulation enables the government to develop appropriate policies that align with the desires and requirements of the community. It also serves as a definitive framework for implementing these policies. In response to the challenges faced in the field of education, the government implemented a zoning strategy as a means to address the issue of educational disparity in Indonesia. The Ministry of Education and Culture (MoEC) has implemented the zoning system as a policy to ensure equitable access to services and high-quality education across the nation. The zoning policy for New Learner Admission (PPDB) is governed by the Minister of Education and Culture Regulation (Permendikbud) No. 14/2018, which supersedes Permendikbud No. 17/2017 on PPDB. There are numerous benefits associated with this zoning policy. One benefit is that it can provide equitable distribution of pupils by assigning them to the school nearest to their residence. Economically disadvantaged learners will have convenient access to education without incurring transportation expenses. Moreover, this zoning policy can facilitate access to educational resources for students, eliminating the need for them to compete with academically advanced peers.